2022
DOI: 10.1051/0004-6361/202244133
|View full text |Cite
|
Sign up to set email alerts
|

COSMOGLOBE: Simulating zodiacal emission with ZodiPy

Abstract: We present ZodiPy, a modern and easy-to-use Python package for modeling the zodiacal emission seen by an arbitrary Solar System observer, which can be used for the removal of both thermal emission and scattered sunlight from interplanetary dust in astrophysical data. The code implements the COBE Diffuse Infrared Background Experiment (DIRBE) interplanetary dust model and the Planck extension, which allows for zodiacal emission predictions at infrared wavelengths in the 1.25–240 µm range and at microwave freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The predicted zodiacal light is then obtained by evaluating a sequence of line-of-sight integrals from the position of the observer and through a model of the three-dimensional interplanetary dust distribution. For implementation details and examples of how to apply ZodiPy to a real-world dataset, see San et al (2022).…”
Section: Statement Of Needmentioning
confidence: 99%
“…The predicted zodiacal light is then obtained by evaluating a sequence of line-of-sight integrals from the position of the observer and through a model of the three-dimensional interplanetary dust distribution. For implementation details and examples of how to apply ZodiPy to a real-world dataset, see San et al (2022).…”
Section: Statement Of Needmentioning
confidence: 99%
“…However, ZL at both 1.25 µm and optical wavelength (ONC-T wide-band) is the scattered sunlight component, and the spectral shape is the same irrespective of ecliptic latitude (Tsumura et al 2010). Therefore, the model ZL brightness at 1.25 µm observed from the Hayabusa2 position was calculated using the ZodiPy code (San et al 2022), and then ZL brightness at the optical wavelength (ONC-T wide-band) was estimated by extrapolating from 1.25 µm using the Solar spectrum (Gueymard et al 2002) as shown in Figure 16 (red). The Gegenschein appears in the antisolar direction, and the Kelsall model does not include the Gegenschein.…”
Section: Absolute Zl Brightnessmentioning
confidence: 99%